2008
DOI: 10.1021/ja803102y
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Columnar Block-Copolymer-Templated Mesoporous Silica via Confined Phase Transformation

Abstract: An efficient method is described for the preparation of phase-pure columnar mesoporous silica nanosystems within the channels of anodic alumina membranes (AAM) via evaporation-induced self-assembly (EISA). Upon the basis of a systematic investigation of the effects of interfacial interactions and different synthesis parameters on the resulting hierarchical mesophase, a salt-induced phase transformation was developed for efficient structural control. Samples with a columnar hexagonal 2D structure along the vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 33 publications
6
72
1
Order By: Relevance
“…Lithium chloride was chosen as the inorganic additive because of its significant effect on the micellar hydration and gelation behavior of PEO-PPO-PEO triblock copolymers in solution. 55,56 The added LiCl indeed had a striking impact on the phase behavior, as the resulting PMO/AAM composites now showed a mesophase with the cubic Im 3m structure (body centered cubic), which is different from the original 2D hexagonal circular mesophase obtained without salt addition. The 2D-SAXS pattern of F127-cubic-200 Bp-PMO (F127-cubic sample calcined at 200 C) shows the typical reflections assigned to the cubic Im 3m phase (Fig.…”
Section: F127-cubic Bp-pmomentioning
confidence: 92%
See 2 more Smart Citations
“…Lithium chloride was chosen as the inorganic additive because of its significant effect on the micellar hydration and gelation behavior of PEO-PPO-PEO triblock copolymers in solution. 55,56 The added LiCl indeed had a striking impact on the phase behavior, as the resulting PMO/AAM composites now showed a mesophase with the cubic Im 3m structure (body centered cubic), which is different from the original 2D hexagonal circular mesophase obtained without salt addition. The 2D-SAXS pattern of F127-cubic-200 Bp-PMO (F127-cubic sample calcined at 200 C) shows the typical reflections assigned to the cubic Im 3m phase (Fig.…”
Section: F127-cubic Bp-pmomentioning
confidence: 92%
“…43 Another reason for the absence of shrinkage might be the added inorganic ions, which have been observed to increase the chemical interactions between organic silica mesophases and the AAM channel surface. 55 The nitrogen sorption isotherm (Fig. 6) of F127-cubic-250 Bp-PMO (F127-cubic sample calcined at 250 C) shows the type IV shape with a broad hysteresis loop that is attributed to the existence of bottlenecks connecting pores in the cubic system.…”
Section: F127-cubic Bp-pmomentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we and others have shown that mesoporous silica channels can be successfully aligned using highly oriented nature of the PAAs membranes [89] shown in figure 8. Samples with a columnar hexagonal 2D structure along the vertical channels of the AAM can be produced with ionic CTAB as template.…”
Section: Vertical Orientationmentioning
confidence: 99%
“…The authors also found a strongly favorable effect of the addition of inorganic salts on the phase-formation process in combination with reduced shrinkage. [19] The kinetics of the mesostructure formation and phase transformations between the two hexagonal phases were investigated by in situ grazing-incidence smallangle X-ray scattering (GISAXS) measurements. [20] Further progress on the way to confined mesoporous organic phases was accomplished by Keilbach et al [21] by synthesizing periodic mesoporous organosilicas (PMOs) in AAM pores.…”
Section: Introductionmentioning
confidence: 99%